SOCIALIZATION TACTICS: LONGITUDINAL EFFECTS ON NEWCOMER ADJUSTMENT. - Ashforth, B. K.; Saks, A. M. (Academy of Management Journal, 1996)
In this longitudinal field study, we used self-report data provided by business school graduates after four months and ten months on new jobs to assess (1) the effects of the six socialization tactics from Van Maanen and Schein's (1979) typology on newcomer adjustment and (2) refinements of existing measures of the investiture tactic and role innovation. Results indicate that the tactics, clustered into an institutionalized (vs. individualized) approach, were negatively related to attempted and actual role innovation, role ambiguity, role conflict, stress symptoms, and intentions to quit and positively related to job satisfaction, organizational commitment, and organizational identification. Self-appraised performance was associated with more individualized socialization.